Upaya Eskalasi Hasil Belajar Matematika Siswa SMA Melalui Implementasi Metode Pembelajaran STAD - Rahayu, Sri (Yayasan Darussalam Bengkulu, 2022)
The learning outcomes of students of 11th Grade of Public Senior High School 1 Mejayan have not achieved satisfactory results, seen from the average daily test scores of 11th grade IPA 1 in odd semester only 51 and the percentage of students who completed only 36.66% of the 30 students there. Factors that influence learning outcomes are students who are less active in classroom learning activities. In an effort to improve student learning outcomes is to apply STAD cooperative learning. This learning method requires students to be able to work together in groups and take responsibility for the success of the group. The purpose of this study was to improve mathematics learning outcomes of students of 11th grade IPA in Public Senior High School 1 Mejayan 1 using the STAD type cooperative learning method. Using an classroom action research method with research subjects 30 students of class 11th grade of Public Senior High School 1 Mejayan in the odd semester of the 2018/2019 academic year. The factors studied are student learning outcomes and implementation of STAD method. The conclusions of the study are: (1) The application of learning by using the STAD type cooperative learning method in 11th grade of Public Senior High School 1 Mejayan can increase student activity in each cycle, student learning activities have met the indicators of success at the second meeting of the second cycle with average the average active students reached 72.41% (2) Implementation of learning using the STAD learning method in 11th grade IPA 1 of Public Senior High School 1 Mejayan can improve student mathematics learning outcomes. Student learning outcomes have met the criteria of mastery learning in the 3rd cycle test with an average student completeness of 83.33%.